Quench, thermalization, and residual entropy across a non-Fermi liquid to Fermi liquid transition - Arijit Haldar; Prosenjit Haldar; Surajit Bera; Ipsita Mandal; Sumilan Banerjee (Physical Review Research, 2020)
We study the thermalization, after sudden and slow quenches, in an interacting model having a quantum phase transition from a Sachdev-Ye-Kitaev (SYK) non-Fermi liquid (NFL) to a Fermi liquid (FL). The model has SYK fermions coupled to noninteracting lead fermions and can be realized in a graphene flake connected to external leads. A sudden quench to the NFL leads to rapid thermalization via collapse-revival oscillations of the quasiparticle residue of the lead fermions. In contrast, the quench to the FL shows multiple prethermal regimes and much slower thermalization. In the slow quench performed over a time τ, we find that the excitation energy generated has a remarkable intermediate-τ nonanalytic power-law dependence, τ^{−η} with η<1, which seemingly masks the dynamical manifestation of the initial residual entropy of the SYK fermions. Our study gives an explicit demonstration of the intriguing contrasts between the out-of-equilibrium dynamics of a NFL and a FL in terms of their thermalization and approach to adiabaticity.